Métodos para o estabelecimento in vitro de Bambusa vulgaris e Dendrocalamus asper - Furlan, Fernanda Cardoso (2016)
The general aim of this study was to evaluate methods of asepsis for the in vitro establishment of B. vulgaris and D. asper. Side branches containing axillary buds and explant sources were collected from field- grown plants. Five experiments were conducted comprising asepsis methods and culture medium preparation with different compositions. In experiment I, four different culture mediums were tested. In experiment II, we evaluated the sterilization procedure and the supplementation with active chlorine and charcoal to the culture medium. In experiment III, we evaluated the application of fungicide via vacuum and its supplementation to the culture medium. Experiment IV aimed at the evaluation of culture medium supplemented with sucrose and BAP. In experiment V, we evaluated the effect of the supplementation of the culture medium with active chlorine and charcoal. In all experiments, we measured the in vitro establishment of nodal segments, percentage of oxidation, fungal and bacterial manifestation, survival and shoot induction (0, 21, 42, and 63 days). Data were analyzed by Shapiro-Wilk and Hartley tests and, when necessary, transformed by Box-Cox test, followed by analysis of variance. Based on the significance level, averages were compared with Duncan’s test or by polynomial, logistic and exponential regression, being the best model selected. The best morphological and physiological results were observed with the MS medium. Charcoal addition implicated in no reduction in oxidation. The addition of active chlorine into the culture medium showed no standard response that could be used to identify the best methods. However, the use of this product reduced bacterial manifestations and the application of the fungicide reduced fungal incidence. Higher concentrations of sucrose increased fungal and bacterial manifestations. The use of BAP promoted higher shoot induction. We were able to develop a protocol for in vitro establishment of nodal segments of B. vulgaris by using explants introduced during 21 days, containing fungicide; followed by subcultures of 42 days in culture medium supplemented with active chlorine, 20 g.L-1 sucrose and 2 mg.L-1 BAP. The use of this methodology revealed higher percentage of in vitro establishment, survival and shoots induction from nodal segments of B. vulgaris. These results might assist in the improvement of asepsis techniques and culture medium management for in vitro establishment of B. vulgaris and D. asper.